Examining the Effectiveness of Lesson Plans for Teaching English Textbooks to Government Elementary Level Students - Nasreen Bugti; Dr. Ishfaque Ali Kalhoro; Dr. Syed Hyder Raza Shah (Indus Journal of Social Sciences, 2025)
Lesson planning is a core part of the effective teaching process, as it is a structured framework that encourages students’ learning, as it plays a key role in enhancing student learning outcomes. The study aims to examine the effectiveness of lesson plans developed by preservice English language teachers for teaching the English textbooks at the elementary level schools in Sanghar. The primary objectives were to identify the challenges teachers face in designing lesson plans and the difficulties they encounter in implementing lesson plans in classroom settings. Quantitative research design was employed to investigate the challenges. Data was collected through structured questionnaires from a sample of 200 government elementary-level schools’ teachers, selected randomly from various schools across the Sanghar district. The questionnaire focused on teachers’ difficulties and experiences related to lesson planning and its implementation. The collected data were analyzed using descriptive statistical methods with SPSS as the analytical tool to determine the mean, median, frequency, and standard deviation. However, findings revealed that a significant number of teachers face challenges, such as insufficient training in lesson planning, limited access to planning resources, time constraints, difficulty in addressing diverse students’ needs, and lack of support from colleagues. Additionally, many teachers reported problems with aligning lessons to textbook objectives and creating engaging and creative classroom activities. This study highlights the urgent need for professional development, better planning resources, and instructional support to enhance the effectiveness of lesson planning. The study points out the necessity of preparing future teachers with structured training on lesson planning to develop instructional qualities; further research is advised that looks into additional strategies for helping preservice teachers develop critical lesson planning capabilities.